2016
DOI: 10.1038/nm.4135
|View full text |Cite|
|
Sign up to set email alerts
|

p53 induces formation of NEAT1 lncRNA-containing paraspeckles that modulate replication stress response and chemosensitivity

Abstract: In a search for mediators of the p53 tumor suppressor pathway, which induces pleiotropic and often antagonistic cellular responses, we identified the long noncoding RNA (lncRNA) NEAT1. NEAT1 is an essential architectural component of paraspeckle nuclear bodies, whose pathophysiological relevance remains unclear. Activation of p53, pharmacologically or by oncogene-induced replication stress, stimulated the formation of paraspeckles in mouse and human cells. Silencing Neat1 expression in mice, which prevents par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
435
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(455 citation statements)
references
References 63 publications
17
435
3
Order By: Relevance
“…Until this point the only way to dissect these two isoforms was to transiently ablate NEAT1_2 with siRNA or ASOs, leaving NEAT1_1 intact (Sunwoo et al 2009;Imamura et al 2014;Adriaens et al 2016). To make a permanent NEAT1_2 knockout line, here we applied a variation on the YFP knock-in strategy used for promoter disruption: We targeted the genomic region closely downstream from the polyadenylation signal of the NEAT1_1 isoform to selectively disrupt NEAT1_2, leaving NEAT1_1 intact ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until this point the only way to dissect these two isoforms was to transiently ablate NEAT1_2 with siRNA or ASOs, leaving NEAT1_1 intact (Sunwoo et al 2009;Imamura et al 2014;Adriaens et al 2016). To make a permanent NEAT1_2 knockout line, here we applied a variation on the YFP knock-in strategy used for promoter disruption: We targeted the genomic region closely downstream from the polyadenylation signal of the NEAT1_1 isoform to selectively disrupt NEAT1_2, leaving NEAT1_1 intact ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NEAT1 transcription can be significantly influenced by p53 and is often up-regulated by stresses, such as hypoxia, viral infection/products, and genotoxic agents (Saha et al 2006;Choudhry et al 2014;Imamura et al 2014;Adriaens et al 2016). Unsurprisingly, there is also a strong link between high NEAT1 expression and more aggressive forms of cancer (Chakravarty et al 2014;Chai et al 2016;Chen et al 2016;Fu et al 2016;Ma et al 2016;Sun et al 2016;Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both NEAT1_1 and NEAT1_2 are induced in an anoxic environment (10). A recent study reports that p53 induces the formation of NEAT1 lncRNA-containing paraspeckles that modulate the replication stress response and chemosensitivity (11). NEAT1 is also a p53-dependent lncRNA in chronic lymphocytic leukemia (12).…”
Section: Introductionmentioning
confidence: 99%
“…As we known, TP53 is involved in many important cellular responses, such as apoptotic cell death, cell cycle arrest, and DNA repair. A recent study reported that TP53 induced formation of NEAT1 lncRNA‐containing paraspeckles that modulated the replication stress response and chemosensitivity (Adriaens et al ., 2016). Consistent with this report, TP53 mutation triggered down‐regulation of NEAT1 expression and resulted in poor response to tamoxifen (Fig.…”
Section: Resultsmentioning
confidence: 99%